2014
DOI: 10.1007/s00590-014-1549-2
|View full text |Cite
|
Sign up to set email alerts
|

Revision of failed anterior cruciate ligament reconstruction with quadrupled semitendinosus allograft: intermediate-term outcome

Abstract: Retrospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…At a mean follow‐up of 5 years (range 2–13 years), the re‐rupture rate was reported to be broad, from 0 to 25%. Among the included studies, only three used allografts exclusively for ACL revision, reporting a re‐rupture rate between 0 and 5% and mid‐term [2, 20, 27].…”
Section: Discussionmentioning
confidence: 99%
“…At a mean follow‐up of 5 years (range 2–13 years), the re‐rupture rate was reported to be broad, from 0 to 25%. Among the included studies, only three used allografts exclusively for ACL revision, reporting a re‐rupture rate between 0 and 5% and mid‐term [2, 20, 27].…”
Section: Discussionmentioning
confidence: 99%
“…12,[31][32][33] In retrospective studies, the mean Lysholm's score for those with revision ACL reconstruction ranged from 58 to 92. 12,19,24,26,27,30,[34][35][36][37][38][39] Two of these studies had control groups for comparison of Lysholm's scores between revision ACLR and primary ACLR cohorts. 36,38 Denti et al found that Lysholm's scores were 57% excellent (95-100 points), 13% good (84-94 points), 22% fair (63-83 points), and 8% poor (<64 points) in 66 patients with revision ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that revision ACL reconstruction has low-complication rates and good clinical results at both short-and midterm follow-up, with significant improvements in knee stability, patient-reported outcome scores, and patient satisfaction. 4,6,9,[23][24][25][26][27] Comparative studies, however, have consistently reported results that are inferior to primary ACL reconstruction. 5,7,8,12 Increased rates of meniscal and chondral pathology may contribute to this discrepancy.…”
Section: Discussionmentioning
confidence: 99%